THE CONCEPT OF MURU’AH ACCORDING TO IBN QAYYIM AL-JAUZIYAH TO INCREASE SELF ESTEEM - Muhammad Raafi Zazuli Muflihu; Hasbi Arijal (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2025)
According to modern Western psychological scientists, self-esteem can be egocentric, i.e., meaning it is unaware that others have feelings and thoughts that are different from its own. There is also an egocentric aspect, namely the imaginary audience which belive that others have a very large concern for them, as much as their do. This study is qualitative research, using a Sufism approach. The method used is deductive analysis method. The conclusions that the researcher makes start from general knowledge about the character's thinking and provide an evaluation on one particular thought. that Muru'ah can be damaged in a person due to the impaired intellect, lack of religion and shame. A good muru'ah reflects noble qualities such as chivalry, steadfastness, courage and self-honor. Then the influence of practicing muru'ah is that it allows us to have self-esteem that is well regraded by others, develop into a respected person, have good social relationships, obey religious teachings, and obtain great social and spiritual benefits.